Working the garden : American writers and the industrialization of agriculture - Conlogue, William (Studies in rural culture., 2001)
In 1860 farmers accounted for 60 per cent of the US workforce; in 1910, 30.5 percent; by 1994 there were too few to warrant a separate census category. This study demonstrates the debates on the changes in family farming that occurred in literature.